2020
DOI: 10.31764/jpmb.v3i2.1893
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Karya Seni Mural Di Pemandian Air Barat Desa Ranggung Sebagai Media Pendukung Berbasis Edukasi Sosial Kemasyarakatan

Abstract: ABSTRAKPembuatan artikel ini bertujuan untuk memberikan edukasi bagi masyarakat dan sebagai bahan referensi dan rujukan bagi desa serta instansi lainnya. Metode pelaksanaan yang digunakan oleh mahasiswa KKN di desa Ranggung melalui berbagai tahapan dan terbagi menjadi beberapa tahap seperti, tahap persiapan, tahap pelaksanaan dan tahap penyelesaian. Pada tahap persiapan mahasiswa melakukan observasi lapangan selama 2 hari yaitu pada hari Rabu dan Kamis pada Tanggal 29-30 Januari 2020, pada tahap pelaksanaan ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research has shown that murals are the object of research both to see the meaning and how this mural represents a group. Research conducted by Vika and her colleagues from Pangkal Pinang regarding the use of murals as a media to support social education revealed that the murals made by KKN students in Ranggung Village contained religious values, social values, and cultural values [8]. Research conducted by Fachmi and colleagues regarding murals in Samarinda City shows that murals are able to carry social messages that are packaged in the form of a work of art in campaigning for awareness about the dangers of smoking in the younger generation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that murals are the object of research both to see the meaning and how this mural represents a group. Research conducted by Vika and her colleagues from Pangkal Pinang regarding the use of murals as a media to support social education revealed that the murals made by KKN students in Ranggung Village contained religious values, social values, and cultural values [8]. Research conducted by Fachmi and colleagues regarding murals in Samarinda City shows that murals are able to carry social messages that are packaged in the form of a work of art in campaigning for awareness about the dangers of smoking in the younger generation [9].…”
Section: Introductionmentioning
confidence: 99%